Unlocking the Potential of Biochar in Drought Stress Tolerance Mechanisms: A Global Bibliometric Analysis (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
This bibliometric review investigates global research trends and scientific productivity in the field of “biochar and drought stress” over a 17-year duration (2009-2025), including 489 records retrieved from 160 journals, books, and proceedings from web of science (WOS) database. This research field shows an annual steady growth rate of 21.14% on an average document age of 3.21 years with 27.83 citations per publication reflecting continuous academic attention and impact. The overall research output comprises 2361 contributing authors, high co-authorship rate of 6.76 authors per document, and 51.12% of studies being international, indicating the global importance and multidisciplinary context of the subject. The collection comprises a broad variety of different document types, with original research articles (410) composing the majority, as well as reviews (56) and other types of contributions. Keyword maps show a conceptual universe of 1,380 authors' keywords and 1,054 Keywords Plus, and themes include soil health, water retention, plant productivity, and resilience to climate. 24,761 References:also demonstrate the depth of the scholarly public interest in employing biochar as a sustainable tool to mitigate drought stress under agroecosystems.
Keywords: Biochar; Bibliometric analysis; Drought; Sustainable tool; Agroecosystems